Measuring the Effectiveness of Lagoon Quest: A Case Study in Environmental Education Program Evaluation - Judith Chen-Hsuan Cheng; Martha C. Monroe; Alison Gordon (EDIS)
Circular 1528, a 33-page full-color report by Judith Chen-Hsuan Cheng, Martha C. Monroe, and Alison Gordon, is a report of the evaluation of the second year of implementing Lagoon Quest in Brevard County, Florida and also a case study of program evaluation, intended to illustrate the program evaluation process and help extension agents and others improve their educational activities. Published by the UF School of Forest Resources and Conservation, August 2008.